1996
DOI: 10.1093/oxfordjournals.eurheartj.a014798
|View full text |Cite
|
Sign up to set email alerts
|

Simple clinical data are useful in predicting effect of exercise training after myocardial infarction

Abstract: Five simple clinical variables, including infarct size, can assist in the selection of patients for exercise training after myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…Carter and Amundsen reported that there was a significant association between infarction size and exercise capacity, 3 whereas Heldal et al found no significant correlation. 16 In the present study, although the peak serum CPK level significantly correlated with exercise capacity in the univariate analysis, the correlation was insignificant in multivariate analysis. This indicates that reduced exercise capacity in Group 1 is caused by factors other than infarction size, that is, prolonged bed rest, an enhanced ventilatory response to exercise (VE/VCO 2 slope), and lung congestion (LVEDP) ( Table IV).…”
Section: Exercise Capacity In Patients With Large MIcontrasting
confidence: 61%
“…Carter and Amundsen reported that there was a significant association between infarction size and exercise capacity, 3 whereas Heldal et al found no significant correlation. 16 In the present study, although the peak serum CPK level significantly correlated with exercise capacity in the univariate analysis, the correlation was insignificant in multivariate analysis. This indicates that reduced exercise capacity in Group 1 is caused by factors other than infarction size, that is, prolonged bed rest, an enhanced ventilatory response to exercise (VE/VCO 2 slope), and lung congestion (LVEDP) ( Table IV).…”
Section: Exercise Capacity In Patients With Large MIcontrasting
confidence: 61%
“…The individual variability regarding the effects of the cardiac rehabilitation programme with exercise therapy is high. Factors to identify the patients who are likely to benefit most from exercise therapy have been studied in sub-populations of cardiac patients [9][10][11][12][13][14][15], but it remains unclear which are the determinants of the improvements in physical exercise performance. Therefore, the present study aimed to identify the determinants of the training effects in cardiac rehabilitation in a large database of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because peak exercise capacity and training-induced changes in peak exercise capacity yield prognostic information [6][7][8], the identification of patients who are likely to benefit most from exercise therapy, would be of interest. A number of groups [9][10][11][12][13][14][15] addressed this question in subpopulations of cardiac patients, but it remains unclear which factors determine the changes in physical exercise performance. Up to now, the predictors for the responsiveness to cardiac rehabilitation have not yet been identified on a general cardiac rehabilitation population.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,14 Hammond et al, 15 van Dixhoorn et al 16 and Heldal et al 17 have reported that the training effect can be predictable from baseline clinical data, baseline fitness, and cardiac status, but they did not evaluate the correlation between an improvement in exercise capacity after ET and hemodynamic or oximetric variables during exercise before ET. In the present study, we measured arteriovenous oxygen content (A-VO2) difference and LV pressure directly during an exercise test at the beginning of ET.…”
Section: Previous Studiesmentioning
confidence: 99%